Biodigestão anaeróbia em duplo estágio do bagaço de cana-de-açúcar para obtenção de biogás - Fernanda Luisa Sampaio de Brito (2011)
Brazil has become one of the largest sugarcane producers, being one of the worlds leaders in ethanol production technology. As ethanol production increases, the total amount of sugarcane bagasse is also increased. Sugarcane bagasse has a great energy potential and is currently considered the Brazilian largest agro-industrial residue. Most of Brazilian sugarcane plants have made the exploitation of bagasse energy through co-generation, which is the burning of bagasse for power generation. In order to obtain a better energy yield from sugarcane bagasse, this research proposes the application of an alternative method of generating energy from this substrate, which constitutes the generation of biogas through anaerobic digestion process, complementing cogeneration currently practiced. The process of anaerobic digestion was carried out in specific pilot plant for digestion of solid material, as Busch & Sieber Patent (2006). We compared the traditional route of power generation (co-generation) and the alternative route (biogas production in pilot plant and later co-generation of processed bagasse in the pilot plant). The comparison between the routes was given by the sum of the energy potential of each one in terms of Net Calorific Value - PCI bagasse and biogas generated per unit mass of sugarcane bagasse. According to the results obtained, in quantitative terms, the potential for power generation (in terms of PCI) was similar in the two routes studied. Considering the substrate on dry basis, an increase of the overall PCI was around 3.5%, while for wet substrate, it was identified a decrease of approximately 22.5% of total PCI. In qualitative terms, the production of biogas per kg of bagasse processed was not significant in comparison with the energy potential of the bagasse processed at the pilot plant (maximum of 1,47% compared to the total potential). Small production of biogas was attributed to the low biodegradability of the bagasse fibers, while the fuel produced was primarily a result of digestion of sugar remaining in the substrate. The substrate samples containing more positive results are those with higher percentage of initial soluble solids, and total reducing sugar, thus competing with the very efficiency of extraction of ethanol